Imaginary selves and shifting signifiers: What's really going on in an online chat classroom? - Cook, Julian (Proceedings of the International Conference on Networked Learning, 2006)
This paper sheds light on what it is about chat rooms that can help or hinder successful learner interaction. Based on a textual analysis of an educational chat room activity it brings together two analytic approaches, critical discourse analysis and Freudian/Lacanian psychoanalysis. It argues that the approaches are complementary, as both look beneath the surface of the linguistic choices made by subjects, and that in combination they can help to reveal the interpersonal dynamics of an interaction. It gives an account of participants getting caught up in interpersonal misunderstandings and envious comparisons, distracting them from their educational purpose, and suggests that this may be linked to the lack of sensory (visual, auditory) information coupled with the time-based nature of chat rooms. It proposes some tactics that might help online educators to avoid these pitfalls.